Reducing risk of childhood obesity in the wake of covid-19. (10th August 2021) - Chung, Alexandra; Tully, Louise; Czernin, Sarah; Thompson, Rachel; Mansoor, Athar; Gortmaker, Steven L
Abstract : Alexandra Chung and colleagues call for governments to prioritise child obesity as they implement measures to recover from the pandemic